Pembinaan Jemaat Sebagai Wujud Peran Gembala dalam Membangun Kedewasaan Rohani - Adelia Tamo Ina; Yeremia Hia (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2025)
Church discipleship is a concrete manifestation of the shepherd's primary role and responsibility within the life of the church. A shepherd is not merely a preacher or worship leader, but a spiritual mentor committed to guiding the congregation toward spiritual maturity. This discipleship process involves various aspects such as deep biblical teaching, personal and communal pastoral care, and continuous discipleship. The main goal is for the congregation to move beyond superficial faith and grow into Christ-like individuals in character, knowledge, and action. This article explores biblical and theological principles of church discipleship and how the shepherd's role must be contextualized to meet the challenges of the present age and the needs of the people. In a world that is constantly changing and spiritually challenging, effective discipleship becomes crucial for the church to remain relevant and spiritually strong. This study affirms that spiritual maturity cannot be achieved instantly, but through a purposeful, consistent process rooted in love and the truth of God's Word. Therefore, discipleship must be a pastoral priority to build a mature, strong, and impactful church.